Penerapan Inovasi Pelayanan Publik Samsat Keliling di Kota Tasikmalaya - Ari Ramdani (Program Studi Administrasi Negara Universitas Serang Raya, 2018)
This research entitled The Innovation of Public Service of SAMSAT in Tasikmalaya City, based on the problem of the need for the administrative services of SAMSAT is so big that it causes long queue or overcrowded so that the duration of society have to wait to get the service. The problem is pneulis meticulously related how the implementation of Public Service Innovation SAMSAT Roving by using a quantitative approach with descriptive methods with respondents Tasikmalaya City community who get the services of SAMSAT Roving. The results of this study indicate that the implementation of public service innovation SAMSAT Roving In Tasikmalaya City run well with the implementation of 3 indicators of innovation public service.